Synthesis and Crystal Structure of Dinuclear Copper(II) Complex with Salamo-Type Ligand - Li, Wen-You; Zhao, Meng-Meng; Li, Gang; Dong, Xiu-Yan (Asian Journal of Chemistry, 2014)
An unexpected dinuclear Cu(II) complex, [Cu2(L2)2] (H2L2 = 3-methoxysalicylaldehyde-O-(2-hydroxyethyl)oxime) has been synthesized through the complexation of Cu(OAc)2·H2O with an asymmetrical Salamo-type compound 6-ethyloxy-6'-methoxy-2,2'-[ethylenediyldioxybis(nitrilomethylidyne)]diphenol (H2L1). The catalysis of Cu(II) ions results in the unexpected cleavage of one of the N-O bonds in the ligand H2L1, giving a novel dialkoxo-bridged dinuclear Cu(II) complex possessing a Cu-O-Cu-O four-membered ring core instead of the usually desired Salamo-type Cu-N2O2 mononuclear complex. In the crystal structure, two intermolecular hydrogen bonds, C2-H2B···O3 and C2-H2B···O4 linked the neighboring molecules into an infinite chain parallel to the a axis.